Recent advances in CAR-T cells therapy for colorectal cancer - Qin, Xiaoling; Wu, Fengjiao; Chen, Chang; Li, Qi (Frontiers in Immunology, 2022)
Colorectal cancer (CRC) is the third most common cancer, with a high mortality rate and a serious impact on people's life and health. In recent years, adoptive chimeric antigen receptor T (CAR T) cell therapy has shown well efficacy in the treatment of hematological malignancies, but there are still many problems and challenges in solid tumors such as CRC. For example, the tumor immunosuppressive microenvironment, the low targeting of CAR T cells, the short time of CAR T cells in vivo, and the limited proliferation capacity of CAR T cells, CAR T cells can not effectively infiltrate into the tumor and so on. New approaches have been proposed to address these challenges in CRC, and this review provides a comprehensive overview of the current state of CAR T cell therapy in CRC.